Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1152/ajpheart.00575.2013
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated exercise pressor reflex in adults with moderately elevated systolic blood pressure: role of purinergic receptors

Abstract: The neurocirculatory responses to exercise are exaggerated in hypertension, increasing cardiovascular risk, yet the mechanisms remain incompletely understood. The aim of this study was to examine the in vitro effectiveness of pyridoxal-5-phosphate as a purinergic (P2) receptor antagonist in isolated murine dorsal root ganglia (DRG) neurons and the in vivo contribution of P2 receptors to the neurocirculatory responses to exercise in older adults with moderately elevated systolic blood pressure (BP). In vitro, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 65 publications
2
71
1
4
Order By: Relevance
“…Patients with hypertension were shown to produce exaggerated BP elevation and enhanced muscle sympathetic nerve activation during isometric handgrip exercise compared with age-related healthy controls [23,24]. Increased muscle metaboreflex activation leading to augmented pressor responses was demonstrated in older moderately hypertensive adults [25] and in pre-hypertensive state [26]. The exercise pressor reflex might occur promptly: BP elevation and heart rate increased within 30-60 sec during static contraction in an experimental study [27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypertension were shown to produce exaggerated BP elevation and enhanced muscle sympathetic nerve activation during isometric handgrip exercise compared with age-related healthy controls [23,24]. Increased muscle metaboreflex activation leading to augmented pressor responses was demonstrated in older moderately hypertensive adults [25] and in pre-hypertensive state [26]. The exercise pressor reflex might occur promptly: BP elevation and heart rate increased within 30-60 sec during static contraction in an experimental study [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the blood pressure response is achieved mainly by a SVR-mediated mechanism rather than by a flow-mediated mechanism (11,42). This scenario has been proposed especially for heart failure, and hypertension and it has been ascribed to excessive sympathetic activation with exaggerated vasoconstriction (7,11,16,22,46,47), although this is not a universal finding (37,50). Results of the present investigation suggest that a similar phenomenon occurs during the metaboreflex in subjects with OMS, with a functional shift from a flow-mediated mechanism to a vasoconstrict-mediated mechanism through which the target blood pressure level is reached.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is tempting to suggest that improvements in metaboreflex function were induced by exercise training in the current study and may be due, in part, to a downregulation of TRPv1 expression to more normal levels. Alternatively, it has been reported that pyridoxal-5-phosphate, a purinergic P2 receptor (P2) antagonist, partially attenuates muscle SNA during postexercise muscle ischemia in moderately hypertensive adults (16). This finding suggests a role for P2 receptors in evoking the exaggerated sympathetic response to activation of chemically sensitive afferent fibers in hypertension (16).…”
Section: Exercise Training Attenuates Responses To Activation Of Chemmentioning
confidence: 99%
“…Alternatively, it has been reported that pyridoxal-5-phosphate, a purinergic P2 receptor (P2) antagonist, partially attenuates muscle SNA during postexercise muscle ischemia in moderately hypertensive adults (16). This finding suggests a role for P2 receptors in evoking the exaggerated sympathetic response to activation of chemically sensitive afferent fibers in hypertension (16). Like the possibility suggested for TRPv1, exercise training may normalize P2 expression reducing metaboreflex overactivity in hypertension.…”
Section: Exercise Training Attenuates Responses To Activation Of Chemmentioning
confidence: 99%